2011
DOI: 10.4081/reumatismo.2006.39
|View full text |Cite
|
Sign up to set email alerts
|

18 month observational study on efficacy of intraarticular hyaluronic acid (Hylan G-F 20) injections under ultrasound guidance in hip osteoarthritis

Abstract: rioramento della cartilagine e del sottostante osso subcondrale; tali fenomeni si riflettono, clinicamente, nel graduale sviluppo di dolore e nella riduzione della funzione articolare (1). La localizzazione coxofemorale dell'artrosi risulta particolarmente frequente, con un'incidenza media variabile a seconda delle casistiche da 88 a 47,3 casi per 100.000 abitanti (2, 3). Il sollievo dal dolore è, tuttora, un obiettivo primario nel trattamento dei pazienti affetti da coxartrosi. Analgesici, FANS, COX-2 inibito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…A number of recent reviews [5,19,54] and a metaanalysis [55] have provided an overview of studies to date of viscosupplementation with HA in hip OA. There is some evidence that efficacy may be greater in cases of less radiographic changes of hip OA [56] and may last up to 3 months post first injection with sustained benefits with further injections [57].…”
Section: Knee Oamentioning
confidence: 99%
See 1 more Smart Citation
“…A number of recent reviews [5,19,54] and a metaanalysis [55] have provided an overview of studies to date of viscosupplementation with HA in hip OA. There is some evidence that efficacy may be greater in cases of less radiographic changes of hip OA [56] and may last up to 3 months post first injection with sustained benefits with further injections [57].…”
Section: Knee Oamentioning
confidence: 99%
“…One of the limitations of HA therapy is that it can be difficult to ensure that the intra-articular injections are actually given into the joint capsule; ultrasound has been used to guide HA administration in hip and hand OA [53,57,87]. years and weight 81 ± 12 kg) with chronic primary or secondary knee OA (of not [12 months old and with a Kellgren and Lawrence radiographic grade of II-IV) and a baseline 0-100 mm VAS score of [30 mm [24].…”
Section: Limitations Of Clinical Evidencementioning
confidence: 99%
“…The latest recommendations of Osteoarthritis Research Society International (OARSI) for the management of hip OA suggest intra-articular therapy with steroids and HA in addition to the standard therapy (Zhang et al, 2010). The hip is a difficult joint to inject, and many studies in the literature show greater safety and precision when the procedure is guided by ultrasound (US) (Migliore et al, 2003; Migliore et al, 2006b). Usually, many HAs with different characteristics are used (Migliore et al, 2016), but a clear priority is given to high molecular weight (MW) HA (Tikiz et al, 2005; van den Bekerom et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…These smaller open-label trials of 10 to 57 participants, without a control group, generally reported moderate improvements in pain and function after treatment with Durolane [28], with Ostenil [26,33], with or Synvisc [25,32]. All studies measured pain (VAS or numerical pain rating scale) or disability (Western Ontario Mac Master scale or Lequesne scale).…”
Section: Discussionmentioning
confidence: 99%